(3TQM aUjM KYdHs - (3YHO Gddg Hf LYaQ Hf OQSJhjI GdfMhis; (3CHh GdYHGS CMeO Hf jMji Hf RjO KYdH GdTjHGfj Gdchaj GdfMhj,J (B291 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdMQef GdQMje GdPi jYKfG HYO MeO Gdgd JYGdi Ydi JUMjM cJGH GdaUjM GdefShH Edi CMeO Hf jMji hJaSjQg JUMjM GdHGH GdChd hgh HGH aYdJ HaJM GdYjf s
(3BNQgG (B:s
(3eY TQM eG CHgeg UGMH GdaUjM hZjQg hEjVGM eG CgedhG hEUdGM eG CaSO heMUhQkG cd Pdc HCHhGH eQJHI hHGddg GdMhd hGdbhI hdg GdWhd hGdefI Je GdcJGH HMeO Gddg hefg hMSf Jhajbg s
(3Ydjg NW GSeGYjd Hf ehghH Hf GdNVQ GdLhGdjbis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs